Journeys through bookland : a carefully coordinated plan for reading applied to the world's best literature - Sylvester, Charles Herbert (The United Educators, 1959)
An eight-volume anthology with selections of graduated reading difficulty includes fables, fairy tales, poems, folklore, and excerpts from longer works. The last volume has an index and a reading plan.